1984
DOI: 10.1002/ijc.2910340421
|View full text |Cite
|
Sign up to set email alerts
|

The differential expression of H‐2K versus H‐2D antigens, distinguishing high‐ metastatic from low‐ metastatic clones, is correlated with the immunogenic properties of the tumor cells

Abstract: Two clones of the 3LL Lewis lung carcinoma, a low-metastatic clone A9 and a high-metastatic clone D122, were studied for MHC expression and immunogenic properties. Using monoclonal antibodies, we demonstrated that the A9 clone expresses both the H-2Kb and the H-2Db, whereas the D122 expresses only the H-2Db, and lacks the expression of the H-2Kb encoded molecules. Cells of the low-metastatic clone A9 grew progressively in syngeneic (C57BL/6J) or in F1 mice, but were rejected in allogeneic recipients. The high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
68
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 17 publications
8
68
0
Order By: Relevance
“…In our own experiments '^^I-3LL cells were lysed in vivo following immunization against D^ but not against K"^, showing that our 3LL line is also K'^-deficient. Eisenbach et al correlated K^-deficiency with poor immunogenicity, since a 3LL clone selected for high K^ expression was more immunogenic in allogeneic mice and showed some indication of immunogenicity in syngeneic mice (7). H-2K expression also appears to be necessary for both induction of CTL and susceptibility to lysis in the response to murine leukaemia virus antigens on syngeneic AKR leukaemias (14).…”
Section: Discussionmentioning
confidence: 99%
“…In our own experiments '^^I-3LL cells were lysed in vivo following immunization against D^ but not against K"^, showing that our 3LL line is also K'^-deficient. Eisenbach et al correlated K^-deficiency with poor immunogenicity, since a 3LL clone selected for high K^ expression was more immunogenic in allogeneic mice and showed some indication of immunogenicity in syngeneic mice (7). H-2K expression also appears to be necessary for both induction of CTL and susceptibility to lysis in the response to murine leukaemia virus antigens on syngeneic AKR leukaemias (14).…”
Section: Discussionmentioning
confidence: 99%
“…Four (Benacerraf, 1981;Linsk & Goodenow, 1986;Schwartz, 1982). The class I MHC molecule consists of three alpha regimes, covalently linked to beta-2-microglobulin (beta 2m), which are encoded by separate genes, and linked prior to expression at the cell membrane (Ploegh et al, 1981;Arce-Gomez, 1978 (Eisenbach et al, 1983;1985). Studies on the expression of human MHC class I antigens in primary vs metastatic tumour are limited; for example malignant melanoma, digestive tract, and laryngeal tumours (Ruiz-Cabello et al, 1989;Esteban et al, 1989).…”
mentioning
confidence: 99%
“…With these immunogenic tumours, those with a high level of MHC antigen expression show low metastatic ability; transfection and subsequent expression of the H2K gene into otherwise highly metastatic H2K-negative tumour cell variants reduces tumour growth, and prevents metastasis (Eisenbach et al, 1983;1985). Studies on the expression of human MHC class I antigens in primary vs metastatic tumour are limited; for example malignant melanoma, digestive tract, and laryngeal tumours (Ruiz-Cabello et al, 1989;Esteban et al, 1989).…”
mentioning
confidence: 99%
“…Actually, in some experiments the low-metastatic, PDGFa receptor negative A9 clone grew faster than the high-metastatic D122 clone in the footpad. This lack of correlation between metastatic phenotype and growth rates of local tumors was demonstrated before in a large group of 3LL clones (Eisenbach et al, 1984).…”
Section: Wild-type Pdgfa Receptor Expressing Clones Are Highly Metastmentioning
confidence: 51%
“…These results suggested there are additional mechanisms contributing to the control of metastatic spread. In our previous studies we have demonstrated that the low metastatic clone A9 expresses much higher levels of MHC class I H-2K b glycoproteins compared to the high metastatic clone D122, resulting in greater immunogenicity of the former (Eisenbach et al, 1984). In fact, immunization of naive C57BL/6 mice with irradiated A9 cells partially retards the development of a subsequent A9 challenge, while immunization with irradiated D122 cells does not a ect the growth of a second D122 tumor (Eisenbach et al, 1984).…”
Section: Wild-type Pdgfa Receptor Expressing Clones Are Highly Metastmentioning
confidence: 97%